Assessment of Knowledge, Attitude and Practices Regarding Hepatitis B Virus Infection Among Sulaimaniyah Registered Dentists: A Cross-Sectional Study - Ali Mohammed Karim Jabary; Abdullah Ezedeen Fakhraldeen; Koraz Kamil Tofiq; Anna Khasraw Mohamed (Penerbit Hellow Pustaka, 2026)
Background: The dental profession faces a significant risk of hepatitis B virus (HBV) contamination, highlighting the crucial role dentists play in controlling HBV cross-contamination. Objectives: To delve into various aspects related to HBV infection control among dentists including assessment of knowledge, examination of preventive measures, and exploration of attitudes. Methodology: In this observational cross-sectional study, a total of 100 dentists were interviewed regarding their knowledge, practice, and attitude towards HBV-positive patients in Sulaimaniyah city, Iraq between January 2024 to 2025. Data collection was carried out using google forms and later was inserted into Microsoft excel and IBM SPSS for analysis. Results: Majority of participants were aged 36-40 years (36%), married (51%), held a Master's degree (42%), had their own clinic (79%), being vaccinated for HBV (87%), received 3 doses of vaccination (61%), checked for antibodies after vaccination (55%), and had 2-7 years in practice (34%). There were a significant association between knowledge, attitude and practice (p=0.000), as 50% exhibited good knowledge, 2% had good attitude, and 20% has good practice. Overall, the majority of individuals had fair to good levels of knowledge, while attitudes and practices toward oral health varied, with a significant portion demonstrating poor levels. Also, a significant association (p<0.05) between knowledge and each of gender, age and qualification were seen, while attitude was significantly related to marital status only (p=0.032), and practice had no significant association with either variable. Conclusion: The strong association between knowledge, attitude and practice has important implications for healthcare policies and interventions. It suggests that improving dentists' knowledge about HBV may positively influence their attitudes towards HBV-positive patients and lead to better practices in terms of patient care and infection control measures.